2004
DOI: 10.1139/h04-016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recovery Mode on Performance, O2 Uptake, and O2 Deficit During High-Intensity Intermittent Exercise

Abstract: Catalogue Data

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
3
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 49 publications
6
64
3
3
Order By: Relevance
“…1,4,33 In the present study, subjects cycled at a relatively low workload of 50 W, which corresponded to 15% to 20% of peak workload achieved during the baseline VO 2peak tests. Although lower than what is generally recommended for optimal lactate clearance, Dorado et al 11 reported that cycling at 20% VO 2peak during recovery improved performance during repeated high-intensity cycling efforts to exhaustion at 120% VO 2peak (lasting approximately 2 minutes, which is similar to the protocol used in the present study). Notably, Dorado et al 11 reported a performance improvement after active versus passive recovery, even though peak blood lactate levels were not different between conditions.…”
Section: Metabolic Markerssupporting
confidence: 46%
“…1,4,33 In the present study, subjects cycled at a relatively low workload of 50 W, which corresponded to 15% to 20% of peak workload achieved during the baseline VO 2peak tests. Although lower than what is generally recommended for optimal lactate clearance, Dorado et al 11 reported that cycling at 20% VO 2peak during recovery improved performance during repeated high-intensity cycling efforts to exhaustion at 120% VO 2peak (lasting approximately 2 minutes, which is similar to the protocol used in the present study). Notably, Dorado et al 11 reported a performance improvement after active versus passive recovery, even though peak blood lactate levels were not different between conditions.…”
Section: Metabolic Markerssupporting
confidence: 46%
“…The reason for the contradiction between the findings of this study and those of Burgomaster et al [6] may be the short duration of training (6 sessions, 2 weeks) and primary VO 2max of the subjects. In addition, the contradiction between this study and Dorado et al [26] may be due to the insufficient volume of exercises, age and gender of the subjects (men aged between 35 and 46).…”
Section: Discussioncontrasting
confidence: 90%
“…Women's CAPT1 (Carnitin Palmitoyltransferaz I) sensitivity to malonyl-CoA in mitochondrial membrane is lower than men which can be a reason for their higher fat burning and WHR decrease in visceral part. Women have higher and more active FABP protein in response to physical activity in their visceral part [26,27]. Researchers have suggested different factors influencing WHR changes such as malonyl-CoA decarboxylase (MCD) changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants performed a 300 m running test to estimate the anaerobic capacity because the anaerobic capacity is the main determinant of performance in maximal efforts between 30 and 60 s. [33][34][35] The test was performed on a 400 m track, and times were chronometered manually. The boys were asked to run maximally the first 300 m.…”
Section: Anthropometry and Body Compositionmentioning
confidence: 99%